Fiscal policy and business cycles - Hansen, Alvin Harvey (London: Routledge, 2003)
Written during the Second World War against the background of the economic and political futility of the 1930s, this book deals with the changing role of government, and particularly fiscal policy as an instrument for regulating the national income and its distribution. Arguing that the war had an economic basis - the inability of the great industrial nations to provide full employment at rising standards of real income - the book discusses how the failure to achieve a world order in the political sphere must be sought in the facts of economic frustration.
Routledge library editions - Economics : Economic theory and econometrics in 6 volumes.
Includes Index and Bibliographical footnotes
rpm 06/06/14
Loans
Keywords: Finance; Business cycles; Economics